PENGARUH RELEVANSI DAN KONSISTENSI TERHADAP LOYALITAS ANGGOTA - kuswanto, kuswanto (Journal MISSY (Management and Business Strategy), 2024)
High loyalty allows PGRI to run its various programs more effectively because it has the full support of its members. This research uses quantitative research methods based on the philosophy of positivism and is applied to research specific populations or samples. Data collection is carried out through research instruments, and data analysis is quantitative, with the aim of testing the hypothesis that has been formulated. With a population of 288 PGRI members in Sukorame District with a sample of 74 members. The results of the existing analysis show that consistency and relevance affect loyalty in different ways. Consistency has a significant positive impact on loyalty, with each unit increase by 762 units. In contrast, relevance is negatively related to loyalty, where each increase of one unit reduces loyalty by 0.231 units. Despite the negative relevance influence, both have a statistically significant influence. Overall, consistency plays an important role in increasing loyalty, while relevance can decrease it.